Non-biological factors associated with postpartum depression among women in Shenzhen: a case-control study - He, Jiangshan; Li, Yang; Chen, Ling; Zhang, Ying (Frontiers in Public Health, 2024)
Background Postpartum depression (PPD) presents a significant public health challenge. While PPD’s impact extends from maternal health to child development, cultural stigma and a lack of public awareness, particularly in developing countries, contribute to its underestimation and under diagnosed. This study investigated the non-biological associated factors for PPD in Shenzhen city due to its unique socioeconomic landscape, where rapid urbanization and migrant influx could uniquely impact maternal mental health. By identifying local PPD determinants, the research aimed to contribute to targeted mental health interventions in the region. Method Data were collected from May to December 2019 at the Luohu Maternal and Child Health Medical Center, Shenzhen. Inclusion criteria were postpartum women without psychiatric histories who live within the locality. The Chinese Edinburgh Postnatal Depression Scale was utilized to confirm PPD diagnosis. Participant information including demographics, economic status and postnatal factors were collected via structured questionnaires. Statistical analyses of t-tests, Wilcoxon rank-sum tests, chi-square tests, and logistic regression, were performed using SPSS 20.0, with significance set at p ≤ 0.05. Results The study included 430 healthy mothers and 73 PPD mothers. Several factors were found to significantly influence the onset of PPD (p < 0.05): age (OR = 0.921, 95% CI: 0.864–0.981); living with in-laws (OR = 2.133, 95% CI: 1.108–4.106); bottle feeding (OR = 3.757, 95% CI: 1.567–9.006); prenatal depression (OR = 3.515, 95% CI: 1.61–7.675); prenatal anxiety (OR = 6.072, 95% CI: 3.209–11.49); and adverse life events during pregnancy (OR = 3.287, 95% CI: 1.165–9.269). Other factors were not found to have a significant effect. Conclusion Our study found that in the developed city of Shenzhen in Southern China, living with in-laws, exclusive bottle feeding, prenatal anxiety, depression, and adverse life events are non-biological associated factors for postpartum depression. The findings emphasize the importance of considering a range of factors when addressing maternal mental health within a specific local regions. It calls for targeted interventions or prevention program that take into considering the specific cultural, social, and individual factors.